A relação do desempenho motor em testes de campo e em situação de jogo no futebol - Rocha, Paulo Ricardo Higassiaraguti [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Technical skills are critical to the success of a team in soccer. Several studies have used isolated from the game context technical skills tests to identify talented players in soccer and differentiate high level players from those of lower level ones. Researchers stress out that testing technical skills can be used to select potential players to play at high levels. However, there is no conclusive evidence on the relationship between the performance shown by the players in a test battery and the performance of the players in a match. The purpose of this study was to examine the performance of soccer players by a battery of tests involving technical skill and performance of these skills during a match. Were selected for the study 36 players of two teams participating in the U-17 in Campeonato Paulista de Futebol 2014. The assessment of technical skills outside the match context was performed by the F-MARC tests. The performance analysis of the players in the match e was held at Soccer Player Assessment Instrument (SPAI). In this study, IAJF had its content validated because it received the minimum acceptable concept (3 of 5) from all experts. Furthermore, SPAI was validated in its intra and inter examiner reliability, with the Spearman's correlation coefficient results (> 0.60) and Kappa agreement ranging from good (0.61 to 0.80) and excellent (0.81 1.0). The performance of players between the two teams in the F-MARC tests showed no significant difference in any of the them. Finally, the results indicated that there is no relationship between performance on specific tests of technical skill and the performance of these skills during a match. In short, the results of this study suggest that the motor evaluation of players who are training to become professional through batteries of tests little expresses the technical skills performed during a match

As habilidades técnicas são fundamentais para o sucesso de uma equipe no futebol. Diversos estudos têm utilizado testes de habilidades técnicas isoladas do contexto do jogo para identificar jogadores talentosos no futebol e diferenciar jogadores de alto nível daqueles de nível inferior. Pesquisadores salientam que testes de habilidades técnicas podem ser utilizados para seleção de jogadores com potencial para atuar em alto nível. No entanto, não há evidência conclusiva sobre a relação entre o desempenho apresentado pelos jogadores em bateria de testes e o desempenho dos jogadores no próprio jogo. O propósito do presente estudo foi examinar o desempenho de jogadores de futebol em uma bateria de testes envolvendo habilidade técnicas e o desempenho dessas habilidades durante uma partida. Foram selecionados para o estudo 36 jogadores de futebol de duas equipes participantes do Campeonato Paulista de Futebol Sub-17 em 2014. A avaliação das habilidades técnicas fora do contexto do jogo foi realizada pela bateria de testes F-MARC. A análise do desempenho dos jogadores no jogo foi realizada pelo Instrumento de Avaliação do Jogador de Futebol (IAJF). No presente estudo, o IAJF foi validado quanto ao seu conteúdo por receber conceito no mínimo aceitável (3 de 5) de todos os especialistas. Além disso, o IAJF foi validado em sua fidedignidade intra e inter avaliadores, com resultados da correlação de Spearman forte (> 0,60) e concordância Kappa que variou entre boa (0,61 a 0,80) e excelente (0,81 a 1,0). O desempenho de jogadores entre as duas equipes na bateria de testes F-MARC não apontou diferença significativa em qualquer dos testes. Por último, os resultados indicaram que não há uma relação entre os desempenhos em testes específicos de habilidade técnicas com o desempenho dessas habilidades realizadas durante um jogo. Em conjunto, os resultados do presente estudo sugerem que a avaliação motora de jogadores que...
Keywords: Soccer; Futebol; Desempenho; Aptidão física; Tecnologia - Avaliação